Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/molehr/gat042
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox gene transforming growth factor β-induced factor-1 (TGIF-1) is a regulator of villous trophoblast differentiation and its expression is increased in human idiopathic fetal growth restriction

Abstract: Abnormal trophoblast function is associated with human fetal growth restriction (FGR). Targeted disruption of homeobox gene transforming growth β-induced factor (TGIF-1) results in placental dysfunction in the mouse. The role of human TGIF-1 in placental cell function is unknown. The aims of this study were to determine the expression of TGIF-1 in human idiopathic FGR-affected placentae compared with gestation-matched controls (GMC), to elucidate the functional role of TGIF-1 in trophoblasts and to identify it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…In our previous studies, we reported that FGR placental villi show an upregulated expression of CGB/βhCG (34,53). The decreased expression of NKX3.1 in FGR, therefore, may have clinical significance in contributing to the premature depletion of the pool of proliferating CTBs by favoring their differentiation.…”
Section: Nkx31 In the Bewo Cell Model For Differentiation Of Trophobmentioning
confidence: 92%
See 1 more Smart Citation
“…In our previous studies, we reported that FGR placental villi show an upregulated expression of CGB/βhCG (34,53). The decreased expression of NKX3.1 in FGR, therefore, may have clinical significance in contributing to the premature depletion of the pool of proliferating CTBs by favoring their differentiation.…”
Section: Nkx31 In the Bewo Cell Model For Differentiation Of Trophobmentioning
confidence: 92%
“…Antibody binding was visualized using horseradish peroxidase-conjugated goat anti-rabbit secondary antibody (Invitrogen/Life Technologies), followed by autoradiography using the ECL-Western Chemiluminescence Detection Kit (GE Healthcare). Total protein load on the gel was determined by Coomassie staining, and the immunoreactive NKX3.1 protein was analyzed by scanning densitometry (ImageQuant, GE Healthcare) as described previously (25,26,33,34).…”
Section: Immunoblottingmentioning
confidence: 99%
“…affected placentae compared with gestation-matched placental controls. However, homeobox genes DLX3, DLX4 and TGIF-1 showed increased expression [34,42,43] in idiopathic FGR-affected placentae compared with gestation-matched controls. Our observation of altered homeobox gene expression levels, i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 79%
“…More specifically, we demonstrated that homeobox gene HLX is expressed primarily in proliferating cytotrophoblast cell types during early placental development [32]. We also determined the expression profile of homeobox gene DLX3 and TGIF-1 in the human placenta [33,34]. In first trimester and term placentae, DLX3 and TGIF-1 localised to the nuclei of villous cytotrophoblast cells, the syncytiotrophoblast layer and proliferating extravillous trophoblast cells in the proximal region of the invading cell columns.…”
Section: Spatio-temporal Expression Patterns Of Homeobox Genes In Thementioning
confidence: 93%
See 1 more Smart Citation